Mostashr al-Dawla’s View of Iran’s Backwardness: A Critical Review on the Book Modernism and Legalism - Mohammad Javad Tahsili,; Maghsoud Ranjbar; Mohammad Torabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Mostashar al-Dawla's treatise “One Word” is one of the most important and original writings of the Qajar period in the field of legalism and on this basis, is the foundation of understanding the idea of legalism in Iran in the Qajar era and also recognizes the lineage of the constitutional movement in Iran. Hamed Ameri has studied this work in his book Modernity and Legalism and this article is a critique of his writing about this book. The most important critique of the book, it is descriptive and the author lacks a critical approach to the work, while the treatise "One Word" by Mostashar al-Dawla can be criticized in various ways, which are discussed in this article and the most important critique of the above treatise is that Mostashar al-Dawla’s has become reductionist in understanding the law and its meaning and this has led to her serious misunderstanding of the place and meaning of law in the modern world. This misconception has had a significant effect on the non-realization of legalism in the contemporary history of Iran.